2018
DOI: 10.1177/2325967118782484
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Participants With a Femoroacetabular Deformity Demonstrate Stronger Hip Extensors and Greater Pelvis Mobility During the Deep Squat Task

Abstract: Background:Cam-type femoroacetabular impingement (FAI) is a femoral head-neck deformity that causes abnormal contact between the femoral head and acetabular rim, leading to pain. However, some individuals with the deformity do not experience pain and are referred to as having a femoroacetabular deformity (FAD). To date, only a few studies have examined muscle activity in patients with FAI, which were limited to gait, isometric and isokinetic hip flexion, and extension tasks.Purpose:To compare (1) hip muscle st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…The total muscle activation also demonstrated an increase for the GMed and the TFL during squat descending and ascending, respectively. Excessive ST activation in symptomatic cam-FAIS during the squat has already been reported [49]. During the descent phase of the squat, the ST acts eccentrically to control the movement, in the FAIS the ST over activates to compensate the hip flexor weakness and allow the task to be performed; as a biarticular muscle, it can be associated with the limited pre-operative pelvic tilt and highlights the muscle unbalance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The total muscle activation also demonstrated an increase for the GMed and the TFL during squat descending and ascending, respectively. Excessive ST activation in symptomatic cam-FAIS during the squat has already been reported [49]. During the descent phase of the squat, the ST acts eccentrically to control the movement, in the FAIS the ST over activates to compensate the hip flexor weakness and allow the task to be performed; as a biarticular muscle, it can be associated with the limited pre-operative pelvic tilt and highlights the muscle unbalance.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies examined the biomechanics of a squat movement or have reported squat data in pre-operative patients with FAIS [38, 45–48]. Four of the previous studies examined maximal squat depth [8, 38, 48, 49], whereas the other study had patients perform a squat to 25% of the total body height at a controlled speed [45]; thus making it difficult to compare our results to the latter. Only two studies had compared squat depth between pre- and post-operative conditions [32, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Cam and pincer morphology have previously been identified in asymptomatic cohorts 2,3 and may have been present in the healthy cohort. To our knowledge, no studies have been published to identify abnormal gait mechanics in asymptomatic individuals with morphological features of FAI, although asymptomatic morphology may be associated with impaired squat mechanics 39 . The purpose of this study was to evaluate sex differences in persons after hip arthroscopy compared with a pain‐free sample without history of hip arthroscopy for symptomatic FAI.…”
Section: Discussionmentioning
confidence: 99%
“…However, biomechanical alterations, including hip and pelvic kinematics, in patients with groin pain and FAI, are inconsistent. While a previous study reported that patients with FAI showed decreased hip flexion angle with increased pelvic posterior tilt during squat motion compared with healthy participants (Catelli et al, 2018), a few others found no difference in hip flexion angle with decreased pelvic posterior tilt (Bagwell et al, 2016;Lamontagne et al, 2009) or decreased hip internal rotation (Bagwell et al, 2016). Moreover, maximum squat did not show any difference in pelvic and hip angles, even though the ipsilateral pelvis rise and hip adduction were increased in patients with FAI in squat with limited pelvic and trunk compensation (Diamond et al, 2017).…”
Section: Introductionmentioning
confidence: 89%
“…According to a recent report on soccer players, there were patients with hiprelated groin pain (impingement-type symptom) despite the absence of abnormal hip morphology (King et al, 2018). Moreover, weaker hip extension muscle strength has been observed in symptomatic patients with cam morphology compared to asymptomatic patients with the same morphology (Catelli et al, 2018). Collectively, hip muscle weakness may affect hip-related groin pain as well as bony deformity during motion, such as the squat.…”
Section: Introductionmentioning
confidence: 99%